2023
DOI: 10.1002/jimd.12664
|View full text |Cite
|
Sign up to set email alerts
|

Fifty years of research on mitochondrial fatty acid oxidation disorders: The remaining challenges

Christine Vianey‐Saban,
Nathalie Guffon,
Alain Fouilhoux
et al.

Abstract: Since the identification of the first disorder of mitochondrial fatty acid oxidation (FAOD) in 1973, more than twenty defects have been identified. Although there are some differences, most FAOD have similar clinical signs, which are mainly due to energy depletion and toxicity of accumulated metabolites. However, some of them have an unusual clinical phenotype or specific clinical signs. This manuscript focuses on what we have learnt so far on the pathophysiology of these disorders which present with clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 193 publications
(284 reference statements)
0
2
0
Order By: Relevance
“…These results suggested that the FFA utilization of the cellular mitochondria was impaired. After the uptake of FFAs, cells activate the carnitine cycle and β-oxidation (FAO), which ultimately provides energy through the tricarboxylic acid cycle (TCA cycle) and oxidative phosphorylation [ 34 ]. Therefore, we further examined the expression of the key enzymes fatty acid transporter 3 (FATP3, a member of the FATP family) and carnitine palmitoyltransferase 1 (CPT1, a rate-limiting enzyme) during the fatty acid uptake and FAO processes.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggested that the FFA utilization of the cellular mitochondria was impaired. After the uptake of FFAs, cells activate the carnitine cycle and β-oxidation (FAO), which ultimately provides energy through the tricarboxylic acid cycle (TCA cycle) and oxidative phosphorylation [ 34 ]. Therefore, we further examined the expression of the key enzymes fatty acid transporter 3 (FATP3, a member of the FATP family) and carnitine palmitoyltransferase 1 (CPT1, a rate-limiting enzyme) during the fatty acid uptake and FAO processes.…”
Section: Resultsmentioning
confidence: 99%
“…Carnitine supply is crucial for energy metabolism as it enables the transport of fatty acids into the mitochondria, where they are oxidized to generate ATP. Although not essential to the body’s supply of carnitine, nutritional sources are very important in humans, with about 75% of total body carnitine originating from food sources, at least in the presence of an omnivorous diet 72 , 73 . The results of our study suggest that humans and some other mammals, having lost a gene coding for an enzyme with efficient HTMLA activity, may have a lower output from the biosynthetic pathway and a higher dietary requirement for carnitine.…”
Section: Discussionmentioning
confidence: 99%